The Effect of Instructional Scaffolders on the Acquisition of Syntactic Concepts among Eighth-Grade Students in Jordan - Al-Zaatreh, Ahmad Shareef; Al-Khawaldeh, Mohammed Ali (Dirasat: Educational Sciences, 2024)
Objectives: The study aims to investigate the effect of instructional scaffolders on acquiring of syntactic concepts among eighth-grade students in Jordan. Methods: The study followed an experimental methodology with a quasi-experimental design. The subjects of the study consisted of (52) eighth-grade students from the “Jjeen” Comprehensive Secondary School for Boys, affiliated with the Education Directorate of Irbid Governorate. They were purposively selected and divided into two groups: 26 students in the experimental group were taught grammatical concepts using educational scaffolds, while 26 students in the control group were taught the same concepts using conventional methods. To achieve the study's objectives, a test of acquiring grammatical concepts consisting of 20 multiple-choice items was prepared. Results: The results of the study revealed statistically significant differences in the acquisition of syntactic concepts among students, attributed to the teaching method favoring educational scaffolds. Conclusions: The study concluded the effectiveness of instructional scaffolders on the acquisition of syntactic concepts among eighth-grade students. In light of the study's results, it recommends several suggestions, notably urging Arabic language teachers to employ educational scaffolders in teaching syntactic concepts to eighth-grade students in Jordan.